Perancangan Interior Flamboyant Ballet School di Surabaya - Sella Wijaya; Grace Mulyono (Intra, 2014)
The interior design of Flamboyant Ballet School in Surabaya aims to provide a forum for residents in Surabaya, especially the ballerina or ballet lovers to delve deeper into the art of ballet and to develop their interests and talents in the world of dance ballet to become a professional ballet dancer. It is therefore necessary to have a facility that can train and support their abilities and talents. The planned facility is a dance studio, auditorium, lobby, shops, cafes, and galleries.